Структурный и параметрический синтез наложенной сети IP/MPLS поверх сети WDM с применением модели, представленной в виде многослойного графа - Агеев, Д. В. (Проблеми телекомунікацій, 2012)
Transport networks are an important components of modern multi-service telecommunication systems. Future technical characteristics of transport networks and their economic efficiency is laid at the design stage. Given article devoted to the structural synthesis problem of IP/MPLS overlay network over WDM network. Route for flows transmission in the transport network can be formed with the use of technology IP / MPLS network, or WDM-network. These technologies have features that results to need the choice between the flexibility of the formation routes and efficient use of bandwidth channels (IP/MPLS technology) and minimizing the network cost by simplifying the hardware of nodes (technology WDM). When solving this problem is given to the choice of bandwidth, transmission routes and topology synthesis together at both levels overlay network. To solve this problem, we use the model as a multilayer graph, as well as flow model for the multilayer graph. The use of models in the form of multilayer graph can adequately describe the structure of the designed network, considering the relationship of processes at its different levels and to provide of describing telecommunications network as a single integral entity. Flow model has allowed to formulate the synthesis problem as a linear programming problem and solved it by using standard optimization software packages. Research of efficiency of the proposed method has shown that this method allows obtaining the structure of the transport network in the 7 - 11% less cost in comparison with the methods based on the sequential design of each level.
Keywords: оптическая сеть; многослойный граф; IP/MPLS; WDM; световой путь